Sob a "lente do espaço vivido": a apropriação das ruas pelos blocos de carnaval na Belo Horizonte contemporânea - Paola Lisboa Côdo Dias (2015)
Street groups of Carnival emerged in Belo Horizonte still at the time of its foundation, in the late nineteenth century. However, although they never totally disappeared, this kind of carnivals que demonstration started decreasing and losing importance from the year 1930 on. Between 1930 and 1980, samba schools and caricatured groups of Carnival were responsible for keeping revelry alive for a few more decades. Nevertheless, in the 1990s, Belo Horizonte became known for its quiet and peaceful atmosphere during this holiday. The first decade of the twenty-first century marks the inflection of this process happens with the emergence of new Carnival associations created by groups of residents in Belo Horizonte. Between 2001 and 2008, some pre-Carnival groups emerged, which attracted more and more revelers to the streets every year, demonstrating it was possible to resume playing Carnival in the capital of Minas Gerais. However, 2009 marks the beginning of the resumption movement of street Carnival groups on the official holiday. Thus, for the past six years, these groups of revelers have been appropriating streets, avenues, squares, lanes, alleys, footbridges, viaducts, slums and squatting places in the city of Belo Horizonte. Therefore, from the early 2000s to the present day, there was a complete transformation of Carnival in the city, from a decadent party, marginalized and almost forgotten by most of the population to an effervescent and exuberant celebration, which took about 1.5 million revelers to the streets in 2015. The proposed object of this research is the appropriation of the streets by Carnival groups in the current context of the city of Belo Horizonte, glimpsing the potential to bring up discussions and original points of view on the categories "space", "urban" and "city" through the appropriation of space by the Carnival party, For this purpose, appropriation is defined as a socio-spatial practice engendered by individual or social groups which, over time, transform nature in the broad sense, not only in its geophysical aspects and biological life, but also societies, the objective and subjective spaces. Furthermore, appropriation is seen as an essential condition for the effective exercise of the Right to the city. Thereby, if the city is the work by praxis, it is through appropriation that it acquires the quality of a socially elaborate and successful space, not only dominated by technique and political power. In order to achieve such a goal, a theoretical tool called Lens of lived space" has been developed, based on the concept of "lived space" by the French sociologist and philosopher Henri Lefebvre (2006). This "lens" is intended to apprehend the social space focusing on the lived space, the one from inhabitants and users of the city. It is the appropriated space in the symbolic and non-verbal level (imagery), which also has its concrete and objective socio-spatial practices that emphasize use and everyday use values. However, analyzing the appropriation of space by the lived perspective does not mean that this dimension can be isolated from the other two dimensions of the production of space proposed by Lefebvre. On the contrary, the purpose of this research is to focus on the dimension of lived space, to analyze dialectically this theoretical triad of the production of space: perceived, conceived and lived. Therefore, the objective of this research is to seek new prospects for research on socio-spatial practices, including those of symbolic and cultural character, which may contribute to eminently spatial analysis, in order to go beyond the current hegemonic approach in partial disciplines dedicated to space, whose studies prioritize its concrete aspects and modes of material production.